Effectiveness of Material Modification of Shear Walls in Reduction of Seismic Vibration Transmission. (2020) - Poul, Libin; Sruthy, S.
Abstract: Damages that happen to any structure during any seismic event can be reduced by imparting inherent damping properties to building elements. Researches have proven that natural fibres exhibit inherent damping capacity. Incorporating the natural fibres to building elements is one way in which damping can be imparted to any building. In building with shear walls, shear walls serve as a major lateral load resisting element when subjected to earthquake loading. This paper studies the effectiveness of incorporating natural fibres to a shear wall in improving the seismic performance. The fibres selected for the study are flax fibre and coconut fibre. These fibres in various percentages are used to modify the shear wall. Hysteresis loops are generated using ANSYS for various percentages of these fibres to study about the energy dissipation capacity of the modified concrete. A building with shear wall is selected, modelled in ANSYS Workbench incorporating the fibres in shear wall alone. A transient analysis is done with El - Centro Earthquake data as the external loading and the responses are compared with that of a building without any modified concrete. The material properties which are required for the analysis in ANSYS Workbench are obtained by conducting experiments. Incorporating the fibres showed a better seismic response than a conventional building without any fibre inclusion, Coir fibre performing better than flax fibre.